Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/dcr.0000000000000568
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Asymptomatic Anastomotic Leakage After Laparoscopic Sphincter-Saving Surgery for Rectal Cancer: Can Diverting Stoma Be Reversed Safely at 6 Months?

Abstract: In the great majority of patients with persistent anastomotic leakage at 6 months after total mesorectal excision, stoma reversal can be safely performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 34 publications
2
37
0
4
Order By: Relevance
“…However, this was likely to have involved a very small number of patients, as Lim and co-workers 28 reported a median time for healing of asymptomatic leaks of 5 months . Similarly, the present authors have reported a mean healing time for asymptomatic anastomotic leakage tracts of 16 weeks 29 . Another limitation of the present study is the short follow-up; longer and multicentre studies are needed to validate the findings.…”
Section: Discussionsupporting
confidence: 82%
“…However, this was likely to have involved a very small number of patients, as Lim and co-workers 28 reported a median time for healing of asymptomatic leaks of 5 months . Similarly, the present authors have reported a mean healing time for asymptomatic anastomotic leakage tracts of 16 weeks 29 . Another limitation of the present study is the short follow-up; longer and multicentre studies are needed to validate the findings.…”
Section: Discussionsupporting
confidence: 82%
“…The results of this study suggest that predisposing factors to recurrent AL following stoma closure are hand‐sewn anastomosis, ischaemia at the anastomotic site, and a shorter interval between confirmation of healing and stoma closure. The overall incidence of recurrent leakage was 13%, which is similar to the rates of 10%–14% in previous studies of similar populations .…”
Section: Discussionsupporting
confidence: 87%
“…This study was prompted by our observation of several leaks from the transverse stapling line of the efferent colonic stump, following restorative rectal cancer surgery, on the CT scan with contrast enema performed before diverting ileostomy closure and by the paucity of available data in the literature. This lack of available information is surprising as side‐to‐end anastomosis (or colonic J pouch) is nowadays the standard of care after TME, as it has been demonstrated to be associated with improved functional results compared to an end‐to‐end anastomosis .…”
Section: Discussionmentioning
confidence: 99%